Moving beyond centre-periphery science: towards an ecology of knowledge - Marginson, S; Xu, X (Centre for Global Higher Education, University of Oxford, 2021)
The evolution of a large and dynamic global system of science has been a major development of the Internet era. The networked system, grounded in autonomous collegial activity, is associated with rapid growth in papers, the spread of science infrastructure to a growing number of countries, and the rise of new science powers outside Euro-America. The United States remains the strongest country in shaping authoritative knowledge but China excels in total papers and in some STEM disciplines.